“Health Care” Thinking Aimed at Protecting Students’ Health as a Pedagogical Necessity (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, the current development of educational processes at the world level, including various socio-pedagogical directions and changes, reforms, a large number of movements, their diversity, the rapid development of the educational system, the increasing demand for the quality of the educational system, the need to protect the health of learners in this process , the issue of the implementation of state policy based on the idea of ​​a healthy generation in our country in a step-by-step, planned, targeted and targeted manner was discussed.